The Effect of Martial Arts Training on Cognitive and Psychological Functions in At-Risk Youths - Harwood-Gross, Anna; Lambez, Bar; Feldman, Ruth; Zagoory-Sharon, Orna; Rassovsky, Yuri (Frontiers in Pediatrics, 2021)
The current study assessed whether an extended program of martial arts training was a viable intervention for at-risk youths in improving cognitive and psychological functions. Adolescent boys attending specialized education facilities for at-risk youths took part in regular sport lessons or martial arts practice twice a week for six months. Hormonal reactivity was assessed during initial training, and measures of psychological (aggression, self-esteem) and cognitive (inhibition, flexibility, speed of processing, and attention) functions were assessed before and immediately following the intervention. Participants in the martial arts training demonstrated significant improvement in the domains of inhibition and shifting and speed of processing. Additionally, initial hormonal reactivity (oxytocin and cortisol) to the intervention predicted significant post-intervention change on several measures of cognitive and psychological functioning. Specifically, oxytocin reactivity predicted improvement in processing speed, as well as reduction of aggression, whereas cortisol reactivity predicted increases in self-esteem. This pioneering, ecologically valid study demonstrates the initial efficacy of this enjoyable, readily available, group intervention for at-risk boys and suggests potential mechanisms that may mediate the process of change.